Hepatic Estrogen Sulfotransferase Distantly Sensitizes Mice to Hemorrhagic Shock-Induced Acute Lung Injury - Xie, Yang; Barbosa, Anne Caroline S; Xu, Meishu; Oberly, Patrick J; Ren, Songrong; Gibbs, Robert B; Poloyac, Samuel M; Song, Wen-Chao; Fan, Jie; Xie, Wen (Endocrinology (Philadelphia), 2020)
Abstract Hemorrhagic shock (HS) is a potential life-threatening condition that may lead to injury to multiple organs, including the lung. The estrogen sulfotransferase (EST, or SULT1E1) is a conjugating enzyme that sulfonates and deactivates estrogens. In this report, we showed that the expression of Est was markedly induced in the liver but not in the lung of female mice subject to HS and resuscitation. Genetic ablation or pharmacological inhibition of Est effectively protected female mice from HS-induced acute lung injury (ALI), including interstitial edema, neutrophil mobilization and infiltration, and inflammation. The pulmonoprotective effect of Est ablation or inhibition was sex-specific, because the HS-induced ALI was not affected in male Est-/- mice. Mechanistically, the pulmonoprotective phenotype in female Est-/- mice was accompanied by increased lung and circulating levels of estrogens, attenuated pulmonary inflammation, and inhibition of neutrophil mobilization from the bone marrow and neutrophil infiltration to the lung, whereas the pulmonoprotective effect was abolished upon ovariectomy, suggesting that the protection was estrogen dependent. The pulmonoprotective effect of Est ablation was also tissue specific, as loss of Est had little effect on HS-induced liver injury. Moreover, transgenic reconstitution of human EST in the liver of global Est-/- mice abolished the pulmonoprotective effect, suggesting that it is the EST in the liver that sensitizes mice to HS-induced ALI. Taken together, our results revealed a sex- and tissue-specific role of EST in HS-induced ALI. Pharmacological inhibition of EST may represent an effective approach to manage HS-induced ALI.